Evaluation of Insecticidal Potentials of Chilli Pepper (Capsicum frutescens L.) and Guinea pepper (Xylopia aethiopica Dun. A. Rich.) in the Control of Bean Weevil (Callosobruchus maculatus L. Fabricus) - Okafor, Kasarachi Patricia; Akunne, Chidi Emmanuel; Nwaoke, Amarachi Joy; Nlemchi, Chukwuebuka Joseph; Okeke, Tobechukwu Ebele; Chidi, Chinaza Alvan; Olisa, Chinemerem Sylvia; Ekwuonu, Ngozi Eucharia; Azaka, Ebele Ijeoma; Mbelede, Kingsley Chinemerem; Offor, Vivian Onyinyechi (CV. Strata Persada Academia, 2024)
This study evaluated the insecticidal potentials of two botanicals, Chilli Pepper (Capsicum frutescens) and Guinea Pepper (Xylopia aethiopica), in controlling the Bean Weevil (Callosobruchus maculatus). The research was conducted at the Laboratory unit of the Zoology Department, Nnamdi Azikiwe University Awka, and the Phytochemical Analysis was carried out at Docchy Analytical Laboratory and Environmental Services Awka, Anambra State. The experiment spanned from December 2023 to February 2024. The efficacy of the botanicals was assessed using a Completely Randomized Design (CRD) method, treating cowpea seeds (Vigna unguiculata) infested with C. maculatus. The study involved the rearing of C. maculatus from a laboratory culture derived from infested cowpea seeds. Experimental cowpea seeds were prepared, sterilized, and treated with various concentrations of the botanical powders. Data on mortality were collected over 120 hours. Phytochemical analysis of the plant materials was conducted using Gas Chromatography with a Flame Ionization Detector (GC-FID) to identify and quantify phytochemicals present in the extracts. Results revealed significant insecticidal properties in both Capsicum frutescens and Xylopia aethiopica. Mortality rates of C. maculatus were observed to increase with higher concentrations of the botanicals, indicating dose-dependent effects. The findings suggest that Capsicum frutescens and Xylopia aethiopica hold promise as natural insecticides for controlling bean weevil infestations in cowpea storage. Further studies are warranted to explore their potential as alternatives to synthetic insecticides, considering their eco-friendly nature and potential benefits in sustainable pest management practices.